Analysis of War and the Rights of Prisoners of War in Islam in Light of Quranic Verses - Mohammad Zereshki (قرآن فرهنگ و تمدن)
In Islam, the fundamental principle is the freedom and dignity of human beings, and captivity is viewed as an imposed and incidental condition on society. Even in situations where social restrictions are applied, such limitations, particularly the capture of prisoners, are solely intended to serve social interests, and not as an act of oppression, but rather as a preventive measure. Islam considers war as a necessity and a last resort, and the philosophy of jihad in Islam aligns with the philosophy of justifiable defense in the United Nations Charter, clearly demonstrating the historical precedence of Islamic humanitarian law over international humanitarian law. The pragmatic approach of Islam, as reflected in the Quranic verses regarding prisoners of war, affirms that humanitarian principles, especially the rights of prisoners of war, have been central to the actions of this religion and its followers in the wars they have faced. The main research question of this study is whether the teachings of Islam regarding war and the rights of prisoners of war are consistent in theory and practice, or whether they conflict. By examining the Quranic verses and narrations (theoretical aspect), as well as the approach of the Prophet Muhammad (PBUH), the Imams (A), and the Islamic armies in warfare (practical aspect), it becomes clear that there is unity in both theory and practice. The research method is descriptive-analytical with a historical approach.